Establishing content validity for a conceptualized instrument to measure barriers to eating a healthful diet in adults: a consensus approach - Enia Zigbuo-Wenzler; Gayenell S. Magwood; Martina Mueller; Angela Fraser (BMC, 2020)
Abstract Background A poor quality diet is a well-known risk factor for many chronic diseases. However, eating a healthful diet is not always simple as many underlying factors can impede adherence. Individuals with fewer barriers are more likely to eat a healthful diet than those who have more barriers. Accurately measuring barriers to eating a healthful diet could inform personalized interventions, particularly those aiming to prevent chronic diseases. The aim of this study was to establish content validity for selected items obtained from the National Health and Nutrition Examination Survey (NHANES) database to be considered for inclusion as items on the conceptualized Dietary Health Status (DHS) instrument, which is designed to measure barriers to eating a healthful diet in adults. Methods The Behavioral Change Wheel hub COM-B and the Theoretical Domains Framework (TDF) were the two theoretical frameworks underpinning the development of the DHS instrument. Seven steps were conducted to create the instrument: 1) development of operational definitions for each TDF domain; 2) identification of items from the NHANES database 2011-2012; 3) screening of items to ensure inclusion of all relevant items; 4) assigning items to a theory-based domain; 5) evaluation of the items against inclusion/exclusion criteria; 6) solicitation of feedback from expert reviewers to reach consensus on inclusion into a domain; and 7) validation of items. Results A total of 170 items representing twelve domains were identified as potential barriers to eating a healthful diet-- knowledge, optimism, beliefs about consequences, beliefs about capabilities, reinforcement, memory, attention and decision processes, environmental context and resources, social influences, emotion, behavioral regulation, health identity, and functional status. Conclusion Expert review consultation and a consensus approach established content validity for 12 theory-based domains comprised of 170 items identified as potential barriers to eating a healthful diet. The use of these explanatory domains may: assist researchers to better understand barriers to adult dietary practices; inform the development of a screening tool that could be used in a community setting to measure barriers to eating a healthful diet; and inform individualized interventions.